АВТОБИОГРАФСКИОТ ДИСКУРС ВО АВТОБИОГРАФИЈАТА НА ГРИГОР ПРЛИЧЕВ (Philological Studies, 2019)
This paper explores the question of autobiographic discourse in Grigor Prlicev’s Autobiography. First, we determine the basic theoretical settings according to which a text can be said to be autobiographical, or having autobiographic elements. Then, it will bespecifically indicated, whether through the presence of explicit and implicit techniques or elements in certain parts used by the author his work can be called an "autobiographical text".
Keywords: autobiography, autobiographical discourse, Grigor Prlicev, Macedonian literature